Influence of vitamin D in bone healing - Freitas, Rafaela Pignatti de; Nunes, Fernanda Parini; Santos, Livia Marcela dos; Weckwerth, Paulo Henrique; Silveira, Elcia Maria Varize; Gulinelli, Jéssica Lemos; Santos, Pamela Leticia (Journal of Oral Diagnosis, 2017)
Introduction: Vitamin D is an hormone whose function is to maintain calcium and phosphorus homeostasis in order to ensure bone mineralization. Vitamin-D deficiency can lead to severe diseases, including an atypical mineralization of bone, because it decreases osteoblasts activity. It has become increasingly common and it has been mainly observed in obese people who avoid direct sunlight exposure to their skin and have a vitamin D-deficient diet. Objectives: Due to the high incidence of hypovitaminosis D in the world population, this study sought to provide an analytical and minute literature review associating vitamin D deficiency with bone healing. Methods: To accomplish this, a bibliographic research was conducted in the following database: Medline (PubMed), Science Direct, Scielo, Periódicos CAPES (Brazilian database), and Bireme (Latin-American database). Results: From the main longitudinal and meta-analytic studies, as well as the main studies conducted on animals, published between 1995 and 2015, 20 articles were selected according to the inclusion criteria. Conclusion: From this review, it was concluded that vitamin D influences the cellular process of bone healing and that the exact mechanism of this influence is still unclear.